Analisis BPJS Kesehatan Ditinjau dari Perspektif Asuransi Syariah - Amelia, Amelia; Siti nur izzati; Purwanto, Muhamad Aji (Syar'Insurance: Jurnal Asuransi Syariah, 2024)
Analysis of BPJS Health from a sharia insurance perspective is an important topic in studying the effectiveness of the health system in Indonesia. This research aims to understand the extent to which the implementation of BPJS Health can be aligned with sharia insurance principles, as well as its impact on public health services. The analysis method includes literature studies related to sharia insurance principles and evaluation of BPJS Health's performance in providing health protection for participants. The results of the analysis show that although BPJS Health has succeeded in providing wider access to health for the Indonesian people, there are still several aspects that are not in line with sharia insurance principles. Some of these include fund management, payment mechanisms, and uncertainty of benefits for participants. This study provides insight into the importance of harmonization between the national health insurance system and sharia values. The implication of this analysis is the need for reform in the structure and operations of BPJS Health to pay more attention to sharia principles in order to increase the effectiveness, fairness and sustainability of the national health system. Further research could focus on implementation strategies that are more in line with sharia insurance principles to improve the health system as a whole.